2017
DOI: 10.1002/jcb.26207
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Interacting Protein SERP1 Regulates the N‐Linked Glycosylation and Function of GLP‐1 Receptor in the Liver

Abstract: Glucagon-like peptide 1 (GLP-1) exerts multiple effects on metabolism through its receptor, GLP-1R, in the liver. Activation and transduction of GLP-1R require complex interactions of largely unknown accessory proteins, and these processes are crucial to the response to endoplasmic reticulum (ER) stress. Using the membrane-based split ubiquitin yeast two-hybrid system (MYTH) and a human liver cDNA library, we obtained the human GLP-1R interactome and identified SERP1 as a potential interacting protein based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…To investigate the potential target genes that induced miR-1-3p biofunction, the TargetScan and miRDB databases were used to analyze related potential genes, and SERP1 was identified as a perspective target. SERP1 was reported to regulate cell proliferation and apoptosis as well as cell membrane stability by increasing glycosylation levels of GLP1R [15]. The protein levels of SERP1 and GLP1R were reduced in the CLP rats' lung tissue compared with the sham group (Figure 4A,B).…”
Section: Serp1 Is the Target Gene Of Mir-1-3p Targetsmentioning
confidence: 94%
“…To investigate the potential target genes that induced miR-1-3p biofunction, the TargetScan and miRDB databases were used to analyze related potential genes, and SERP1 was identified as a perspective target. SERP1 was reported to regulate cell proliferation and apoptosis as well as cell membrane stability by increasing glycosylation levels of GLP1R [15]. The protein levels of SERP1 and GLP1R were reduced in the CLP rats' lung tissue compared with the sham group (Figure 4A,B).…”
Section: Serp1 Is the Target Gene Of Mir-1-3p Targetsmentioning
confidence: 94%
“…GPCRs have been found to also interact with other membrane and/or intracellular proteins in addition to heterotrimeric G proteins, GRKs, and β-arrestins. These so-called GPCR interacting proteins (GIPs) can mediate and/or modulate GPCR signaling and/or trafficking [16][17][18], and have been identified by various biochemical (e.g., pull-downs from cell lysates using Glutathione S-transferase (GST) or His6-tagged GPCR C-tails [19,20], or HDL-reconstituted GPCR [21]), cell biological (e.g., ascorbate peroxidase (APEX)-catalyzed proximity labeling in living cells followed by affinity chromatography, enzyme digestion, and mass spectrometric analysis [22][23][24]), and genetic approaches (e.g., membrane yeast two-hybrid (MYTH) [25][26][27][28][29][30][31]).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 GLP-1 analogue, Exendin-4 (Ex-4), has been used in clinical treatment of type 2 diabetes mellitus (T2DM). 12,13 Recent studies have found that GLP-1 promotes the phosphorylation of AMPK in hepatocytes and reduces the glucose content of hepatocytes in diabetic mice. 13 Other studies showed that exenatide had direct protective effects on endothelial cells through the AMPK/Akt pathway in a GLP-1 receptor-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Recent studies have found that GLP-1 promotes the phosphorylation of AMPK in hepatocytes and reduces the glucose content of hepatocytes in diabetic mice. 13 Other studies showed that exenatide had direct protective effects on endothelial cells through the AMPK/Akt pathway in a GLP-1 receptor-dependent manner. 14,15 However, the interaction of GLP-1 and AMPK in the treatment of diabetes is not clear.…”
Section: Introductionmentioning
confidence: 99%